PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI BARISAN DAN DERET SISWA KELAS XI SMA NEGERI 8 KOTA JAMBI - Pitria Arpani; Buyung Buyung; Relawati Relawati (Universitas Batanghari Jambi, 2019)
This research is a Research and Development (R & D) research that aims to produce a product in the form of mathematics LKS based on Contextual Teaching and Learning in the sequence and series material seen from the criteria, practicality, validity and effectiveness. This research was conducted to provide one of the learning resources in the form of learning tools that support the 2013 curriculum implementation in SMA Negeri 08 Jambi City.This study refers to the ADDIE development model which includes five stages: analysis, design, development, implementation and evaluation, and the subjects used in this study are (a) validation sheets for experts material, design experts and media experts who function to determine the validity of worksheets, (b) student response questionnaires which function to determine the practicality of LKS and (c) post-test questions that function to determine the effectiveness of LKS.The results showed that worksheets based on contextual teaching and learning in the class and sequence material of class XI students were categorized as good and suitable to be used as a learning tool seen from the results of expert validation which obtained an average score of 4.3 with a percentage of 86%, classified in the category practically seen from the results of the questionnaire responses of students who received an average score of 4.37 with a percentage of 80%, and classified as effective as seen from the calculation of students' completeness of the post-test questions that obtained an average score of 0.925 with a percentage of 92.5%.Keyword:Development, Student Worksheet (LKS), Contextual Teaching andLearning (CTL), ADDIE